2019
DOI: 10.1037/cbs0000142
|View full text |Cite
|
Sign up to set email alerts
|

Implicit attitudes about gender and emotion are associated with mothers’ but not fathers’ emotion socialization.

Abstract: The present study tested whether mothers and fathers differed in their implicit attitudes about the expression of sadness and anger in middle childhood boys and girls (ages 8 -12) and whether these implicit attitudes are associated with emotion socialization practices. Two implicit association tests (IATs) focusing on children's expression of sadness (sad) and anger (ang) were developed. A total of 302 and 289 parents completed the IAT sad and IAT ang , respectively, and parents self-reported on their explicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…For example, R. M. Martin and Green (2005) found that preschool boys’ emotion understanding was strengthened through maternal use of emotion talk and cause‐focused explanations, which are characteristics of emotional coaching. In general, boys may receive less support for negative emotions than girls (Thomassin & Seddon, 2019). Mothers also may spend less time talking about the contexts of emotions with boys (Fivush et al., 2000) and using less emotion talk with boys (Cassano et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, R. M. Martin and Green (2005) found that preschool boys’ emotion understanding was strengthened through maternal use of emotion talk and cause‐focused explanations, which are characteristics of emotional coaching. In general, boys may receive less support for negative emotions than girls (Thomassin & Seddon, 2019). Mothers also may spend less time talking about the contexts of emotions with boys (Fivush et al., 2000) and using less emotion talk with boys (Cassano et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, a seminal study by Culp et al (1983) showed that mothers, unlike fathers, possessed low awareness of their gendered behaviour towards infants. One's awareness of biases, and the implicit versus explicit nature of biases, is relevant because it is proposed that explicit biases, which lie within one's conscious awareness, are more amenable to change (Thomassin & Seddon, 2019). Therefore, fathers may have accessed and reflected upon their gendered beliefs more easily than mothers.…”
Section: Kmb: a Unique Effect For Fathersmentioning
confidence: 99%
“…First, we hypothesized that the KMb condition (vs. the control condition) would be more effective at impacting, or reducing, parents’ gendered beliefs. We further tested for parent gender, expecting that access to implicit and explicit beliefs about gendered emotion expression would be more salient to fathers and thus would be more malleable in fathers (Thomassin & Seddon, 2019). It was hypothesized that parent emotion dysregulation might prevent parents from fully engaging with the material in the KMb video, and therefore, parents high in emotion dysregulation may not respond as strongly to the KMb as parents endorsing low emotion dysregulation.…”
Section: Parents’ Gendered Emotion Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing that gender may impact perceptions of social others, we additionally considered whether there exist differences in men and women's responses to the PSI scales. Gender differences appear across a range of topics related to social intelligence, including implicit beliefs about acceptable emotion expression in childhood [Thomassin and Seddon 2019 ], beliefs about the impact of body appearance on social standing [Wang et al 2019 ], and perceptions of threat and attractiveness based on facial expressions [Hester 2019 ]. Men and women also differ in how they perceive technology.…”
Section: Item Selectionmentioning
confidence: 99%